LMNO pea-quel - Baker, Keith, 1953- (New York : Beach Lane Books, 2017)
Busy little peas introduce more of their favorite occupations and activities, from actor to zipper on a zip line.
Keywords: Stories in rhyme; Peas -- Fiction; Occupations -- Fiction; Alphabet; JUVENILE FICTION / Concepts / Alphabet; JUVENILE FICTION / Business, Careers, Occupations; JUVENILE FICTION / Stories in Verse